2021
DOI: 10.1016/j.asmart.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional CT analysis of the change in rotational alignment in double level osteotomy after double level osteotomy performed for varus osteoarthritic knees

Abstract: Purpose To analyze the change in rotational alignment caused by double level osteotomy (DLO) based on comparative three-dimensional image analysis of pre- and postoperative CT images. Methods Pre- and postoperative CT examination of the lower extremities were performed with informed consent for 39 consecutive knees undergoing DLO for varus knee deformity. The DLO procedure consisted of closed wedge distal femoral osteotomy (CWDFO) and open wedge high tibial osteotomy (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the other hand, the use of patient-specific simulations and personalized guides provides a reliable method to ensure unchanged rotation with DFO. In contrast, the orientation of bone cuts in BP DFO inevitably leads to unwanted rotational changes in the axial and sagittal planes [8,9]. This justifies the use of patient-specific instruments for the DCC configuration, as they help overcome the limitations associated with freehand techniques and ensure accurate and precise execution of the osteotomy [25][26][27].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of patient-specific simulations and personalized guides provides a reliable method to ensure unchanged rotation with DFO. In contrast, the orientation of bone cuts in BP DFO inevitably leads to unwanted rotational changes in the axial and sagittal planes [8,9]. This justifies the use of patient-specific instruments for the DCC configuration, as they help overcome the limitations associated with freehand techniques and ensure accurate and precise execution of the osteotomy [25][26][27].…”
Section: Plos Onementioning
confidence: 99%
“…Studies found that the torsional stability of BP DFO was less than that of single plane DFO [ 5 ], and the anterior flange of the BP osteotomy was prone to fracture [ 6 , 7 ]. Furthermore, the studies by Nakayama et al and Kambara et al showed that BP DFO generates internal rotation and flexion due to the mismatch of the two transverse cuts [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%